CdS-Sensitized TiO2 Nanotube Arrays: Preparation and Enhanced Photocatalytic Activity - Yuan, Yunsong; Li, Lingjie; Lei, Jinglei; He, Jianxin; Xu, Jing; Zhang, Shengtao (Asian Journal of Chemistry, 2014)
CdS-sensitized TiO2 nanotube arrays (CdS-TNTAs) were prepared by depositing CdS into the crystallized anodic TiO2 nanotube arrays via sequential chemical bath deposition (S-CBD) method. Characterizations via XPS and FE-SEM show that the CdS nanoparticles, approximately 20-30 nm in diameter, were deposited on TiO2 nanotubes arrays. UV-visible absorption spectra illustrate that sensitizing TiO2 nanotubes with CdS extends the absorption response of TiO2 nanotube arrays into the visible region. The photocatalytic efficiency of CdS-TNTAs is significantly enhanced as compared to the pristine TiO2 nanotube arrays, which can be attributed to the deposition of CdS effectively stimulating the charge separation and thus hindering the recombination of electron/hole pairs of TiO2 nanotube arrays. It is also demonstrated that the CdS deposition condition, such as the immersion time and cycles of sequential chemical bath deposition treatment, has important impacts on improving the photocatalytic efficiency of CdS-TNTAs. The appropriate immersion time (e.g. 5 or 10 min in the present work) and cycles (e.g. 2 or 1 cycle) of sequential chemical bath deposition process benefit the photocatalysis greatly.